2017
DOI: 10.1136/bmjpo-2017-000216
|View full text |Cite
|
Sign up to set email alerts
|

Preterm infant outcomes in relation to the gestational age of onset and duration of prelabour rupture of membranes: a retrospective cohort study

Abstract: ObjectiveTo determine the hospital outcomes of liveborn infants at 23–31 weeks following prelabour preterm rupture of membranes (PPROM).MethodA regional retrospective cohort study of 4454 infants of 23–31 weeks’ gestation admitted to a tertiary neonatal network between 2007 and 2011. Primary outcome was the composite chronic lung disease (CLD) or mortality at discharge.Results225 (5%) neonates had a history of PPROM occurring prior to 24+0 weeks (Early-PPROM), 829 (19%) had a history of PPROM at or after 24+0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
3
5
2
1
Order By: Relevance
“…These differences were still significant after subgroup analysis with the consideration of hypertensive disorders distribution. This was not observed in the Pharande et al study, but comparable results were obtained by other authors [8,14].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These differences were still significant after subgroup analysis with the consideration of hypertensive disorders distribution. This was not observed in the Pharande et al study, but comparable results were obtained by other authors [8,14].…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, Pharande et al observed lower prevalence of hypertensive disease of pregnancy in patients with pPROM www. journals.viamedica.pl/ginekologia_polska than with the intact membranes (7.6% vs 26.7%) [8]. Hypothyroidism was also more prevalent in the group without pPROM (19.4% vs 28.7%), which stands in contrast to results of other studies.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Meanwhile, risk factors for neonatal BPD during pregnancy include intrauterine growth restriction and chorioamnionitis [ 24 ]. One study reported that the incidence rate of BPD was higher in cases who experienced pPROM before 31 weeks of gestation than those who did not experience the condition [ 27 ], Another study reported that from among 36 neonates who were born to mothers diagnosed with pPROM before 24 weeks of gestation and who were discharged following delivery, 17 (47%) developed BPD [ 28 ]. Oligohydramnios was found to be a risk factor for BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, risk factors for neonatal BPD during pregnancy include intrauterine growth restriction and chorioamnionitis (21). One study reported that the incidence rate of BPD was higher in cases who experienced pPROM before 31 weeks of gestation than those who did not experience the condition (24), Another study reported that from among 36 neonates who were born to mothers diagnosed with pPROM before 24 weeks of gestation and who were discharged following delivery, 17 (47%) developed BPD (25).…”
Section: Discussionmentioning
confidence: 99%